Analisis Persepsi Risiko Pekerja di Indonesia Terhadap COVID-19 - Dzikri Robbi; Mewati Ayub; Setia Budi (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
Since August 2020, the COVID-19 pandemic has affected more than 29 million workers in Indonesia. Therefore, worker protection and job creation must be an important priority to emerge more resilient and productive after the COVID-19 crisis. Threat assessment and risk perception are core features of protective-motivation theory and understanding workers' perceptions of COVID-19 risk is expected to help navigate and manage the impact of this pandemic on workers. This study assesses workers' risk perceptions of COVID-19 using a national sample of size N=1,900 of workers in Indonesia. The level of employee risk perception of COVID-19 is relatively high in all workplaces and the workplace also influences the level of risk perception. From all respondents, it is known that the respondent's knowledge about COVID-19, the respondent's behavior towards COVID-19 and the social environmental conditions at the respondent's workplace are all significant predictors of the perceived risk of COVID-19. Age group and type of workplace were found to be significant determinants of perceived risk, compared to the sex and employment status of the examined workers. In all workplaces, respondents stated that the risk of spreading COVID-19 was at a moderate level and the work area was considered an area that had a higher risk of spreading COVID-19 compared to smoking areas and the canteen or pantry.